1971
DOI: 10.1007/bf02250901
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a cyclonic storm on the energy fluxes at the urban interface — A preliminary experiment

Abstract: SummaryThe spatial and temporal variations of the energy and moisture budgets of a megalopolis (Los Angeles basin) were examined during a frontal passage February 23, 1969) and during an extremely clear day (March 4, 1969) in order to determine the existing continuum of possible extremes during that season. The distributional aspects of solar radiation (direct and diffuse), reflected solar radiation, net radiation, latent heat flux, sensible heat flux, and heat flux in or out of the urban interface were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Few urban energy balance measurements are available for comparison with the Myrup and Morgan study. Terjung [1969Terjung [ , 1971 during a cloudy, a rainy, and a clear day. However, owing to the paucity of fixed observation points, the traversing techniques used, and the need to compute the sensible heat flux as an energy balance residual, it is difficult to draw firm conclusions from these preliminary studies (W. H. Terjung, personal communication, 1973).…”
Section: Assuming a Constant Flux Layer Of 200 M And Appropriate Metementioning
confidence: 99%
“…Few urban energy balance measurements are available for comparison with the Myrup and Morgan study. Terjung [1969Terjung [ , 1971 during a cloudy, a rainy, and a clear day. However, owing to the paucity of fixed observation points, the traversing techniques used, and the need to compute the sensible heat flux as an energy balance residual, it is difficult to draw firm conclusions from these preliminary studies (W. H. Terjung, personal communication, 1973).…”
Section: Assuming a Constant Flux Layer Of 200 M And Appropriate Metementioning
confidence: 99%
“…MEASUREMENT When investigating heat storage uptake and release from facets of the urban system such as roads, roofs, walls, and open land, it is appropriate to use standard heat flux plates (e.g., Nunez and Oke, 1977). One or more plates have also been used to represent heat storage in studies of the areally-averaged energy balance of a city (e.g., Terjung et al, 1971;Kerschgens and Hacker, 1985;Kerschgens and Drauschke, 1986). Unless a very wide variety of surface materials and orientations is sampled, the approach seems open to serious error.…”
Section: Introductionmentioning
confidence: 99%
“…Terjung et al (1971) have found a value of 35 % during the study of one clear day in Los Angeles. No water was present on the pavement during the days of this study so evaporation was not a factor in the energy budget.…”
Section: The Energy Budgetmentioning
confidence: 93%